Lactate Dehydrogenase as a Biomarker for Assessment of COVID-19 Prognosis in Severe and Critically Ill Patients in Nepal: A Single-centered Retrospective Study (One Health Journal of Nepal, 2023)
Introduction: COVID-19 is an infectious disease caused by a corona virus. The level of serum LDH has been observed to be an important biomarker in predicting the extent of lung tissue damage. This study aimed to further investigate the predictive accuracy of LDH in estimating the prognosis of critically ill patients.Methods: A retrospective study was conducted among COVID-19 patients, ≥ 18 years admitted to the intensive unit of Nepal APF Hospital from July 2020 to November 2021. Ethical approval was taken from NHRC and non- random sampling technique was done. The demographic, clinical and baseline LDH data was collected from the admission record files. The clinical status was investigated to look for discharge or death in the ICU. Thosepatients who were discharged or transferred to step-down were recorded as surviving patients. Data was entered in Microsoft Excel and analyzed using SPSS v16.Results: Out of 190 patients 63% were males. The mean age noted was 56.59 ± 15.706 years. The duration of ICU stay was 9.13 ± 5.392 days. Among them 103 died and 87 of them survived. The cut-off value of LDH as a prognostic marker for mortality was observed to be 450 IU/L. On ICU admission, 164 patients had high LDH. Higher mortality was observed in the high LDH group (56%) as compared to the low LDH group (42.3%).Conclusions: LDH is a useful biomarker for predicting in-hospital mortality in severe and critically ill COVID-19 patients and can guide the treating physicians to approach and plan the clinical management of patients with severe disease.